Finite Element Simulation of Medium-Range Blast Loading Using LS-DYNA - Yuzhen Han; Huabei Liu (Shock and Vibration)
This study investigated the Finite Element simulation of blast loading using LS-DYNA. The objective is to identify approaches to reduce the requirement of computation effort while maintaining reasonable accuracy, focusing on blast loading scheme, element size, and its relationship with scale of explosion. The study made use of the recently developed blast loading scheme in LS-DYNA, which removes the necessity to model the explosive in the numerical models but still maintains the advantages of nonlinear fluid-structure interaction. It was found that the blast loading technique could significantly reduce the computation effort. It was also found that the initial density of air in the numerical model could be purposely increased to partially compensate the error induced by the use of relatively large air elements. Using the numerical approach, free air blast above a scaled distance of 0.4 m/kg1/3 was properly simulated, and the fluid-structure interaction at the same location could be properly duplicated using proper Arbitrary Lagrangian Eulerian (ALE) coupling scheme. The study also showed that centrifuge technique, which has been successfully employed in model tests to investigate the blast effects, may be used when simulating the effect of medium- to large-scale explosion at small scaled distance.